Absence of genotoxicity of purified Aloe vera whole leaf dry juice as assessed by an in vitro mouse lymphoma tk assay and an in vivo comet assay in male F344 rats. (2021) - Hu, Jiang; Lloyd, Mel; Hobbs, Cheryl; Cox, Peter; Burke, Keith; Pearce, Gareth; Streicker, Michael A.; Gao, Quanyin; Frankos, Vasilios
Graphical abstract: Abstract: Hydroxyanthracene derivatives (HAD) are naturally present in the latex layer of Aloe vera leaf, predominantly as aloins A, B and aloe-emodin. HAD are typically removed from commercial ingestible aloe products through activated charcoal filtration (decolorization). Current research aimed to evaluate genotoxic potential of a purified aloe whole leaf dry juice containing 0.3 ppm of total aloins and non-detectable aloe-emodin (LOD =0.01 ppm) in the L5178Y mouse lymphoma assay (MLA; OECD 490) and in vivo comet assay (OECD 489). No marked increases in mutant frequency at the tk locus were observed in the MLA at concentrations up to 5000 μg/mL for 3 h and 24 h (-S9), and up to a precipitating concentration of 3000 μg/mL for 3 h (+S9) compared to concurrent vehicle control. Relative total growth at the highest analyzable concentrations at 3 h (±S9) and 24 h (-S9) ranged from 64 to 133 %. In the comet assay, no statistically significant increases in DNA strand breaks were detected in the colon or kidney following oral gavage of 500, 1000 or 2000 mg/kg/day in male F344 rats for 2 days compared to concurrent vehicle control. Overall, these findings demonstrated the test article containing minimal HAD is not genotoxic under the described experimental conditions.